Post-Stroke Oculomotor Nerve Palsy Treated by Traditional Korean Medicine: Three Case Reports - Lee, Yoo-na; An, Yu-min; Jang, Woo-seok; Baek, Kyungmin (대한한방내과학회지, 2019)
Post-stroke oculomotor nerve palsy occurs more frequently than previously reported, but only a few studies of traditional Korean medicine treatments have been reported. The symptoms are severe and difficult to treat, and current treatments are high-cost, short-lasting, insufficient for shortening the therapeutic period and promoting better recovery, or involve the risk of post-operative over-correction or under-correction. Traditional Korean medicine treatments may be comparatively effective at lower cost and less harmful. Thus, we report three cases of post-stroke oculomotor nerve palsy treated with traditional Korean medicine.